Endovascular Treatment for Acute Thromboembolic Occlusion of the Superior Mesenteric Artery and the Outcome Comparison between Endovascular and Open Surgical Treatments: A Retrospective Study. (24th October 2017) - Zhang, Zhao; Wang, Dan; Li, Guoxun; Wang, Ximo; Wang, Yuxiang; Li, Gang; Jiang, Tao
Abstract : We reported our experience with endovascular treatment for patients with acute thromboembolic occlusion of the superior mesenteric artery (ATOS) as well as comparing the efficacy between endovascular and traditional open surgical treatments. Eighteen consecutive patients with ATOS who received endovascular treatment and 12 patients who received open surgical treatment between February 2007 and October 2012 at Tianjin Union Medical Center (Tianjin, China) were retrospectively reviewed. Primary clinical outcomes included the technical success, requirement of laparotomy, length of bowel resection, perioperative mortality within 30 days, and surgical complications. The patients were followed up for 0.1 to 98 months. For patients who underwent endovascular treatment, complete technical success was achieved in 8 (44.4%) patients and partial success was achieved in the remaining 10 (55.6%) patients. Laparotomy was required in 6 (33.3%) patients. The 30-day mortality was 16.7%. In comparison to open surgical therapy, endovascular therapy achieved lower requirement of laparotomy (in 33.3% versus in 58.3% of cases, p = 0.18 ), significantly shorter average length of bowel resection (88 ± 44 versus 253 ± 103 cm, p = 0.01 ), and lower mortality rate (16.7% versus 33.3%, p = 0.68 ). The endovascular therapy is a promising treatment alternative for ATOS.